Transport Problem in the Transnistrian Settlement: “Coercive Diplomacy” Instead of “Small-step Tactics” - N. V. Shevchuk (Евразийская интеграция: экономика, право, политика, 2020)
The author analyzes new complications that have arisen in the Moldovan-Transdnistrian process, highlighting the problem concerning freedom of movement of people, goods and services and showing the reasons that led to the exchange of so-called transport sanctions. Particular attention in the article is paid to the Ukrainian factor and the issue of organizing a joint Modavan-Ukrainian border and customs control on the Transdnistrian section of the border. According to the author, the suspension of mutual transport sanctions by the parties to the aggrieved parties is temporary, and the unilateral change made byMoldovain current regime of foreign economic activity of the Transdnistria's economic entities will serve as a new impetus for the escalation of the conflict. Moldova will use the innovation as a “stick” in order to encourage Transdnistrian enterprises to transfer transdnistrians also to the transport jurisdiction of Moldova, that is, to obtain Moldovan license plates, Moldovan driver’s licenses and other related documents to replace Transdnistrian ones. In addition, the author comes to the conclusion that the role ofRussiais weakening in the process of normalization of the Transdnistrian-Moldavian relations and in the conflict region.